The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.15294/jhe.v6i1.45307
|View full text |Cite
|
Sign up to set email alerts
|

Cyberloafing Behaviors of Health Professional Students during Distance Education in the COVID-19 Pandemic Period

Abstract: Background: With the declaration of the new coronavirus (COVID ‐ 19) pandemic, which was detected in the Wuhan region of China and later seen in many countries of the world, education and training were significantly affected in all countries, and distance education started to be used in all areas of education. To this end, students can exhibit cyberloafing behaviors during distance education for various reasons. Thus, this study aims to determine the levels of cyberloafing and the factors affecting these beh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…For example, Zhou et al (2021) found that hindrance stressors affect cyberloafing through the mediating role of emotional exhaustion. To the best of our knowledge, stressors related to COVID-19 and cyberloafing have not yet been examined; however, recent work by Ozdemir et al, 2021 , Chavan et al, 2021 suggests that cyberloafing is a common phenomenon among students during remote in the current pandemic.…”
Section: Theoretical Frameworkmentioning
confidence: 99%
“…For example, Zhou et al (2021) found that hindrance stressors affect cyberloafing through the mediating role of emotional exhaustion. To the best of our knowledge, stressors related to COVID-19 and cyberloafing have not yet been examined; however, recent work by Ozdemir et al, 2021 , Chavan et al, 2021 suggests that cyberloafing is a common phenomenon among students during remote in the current pandemic.…”
Section: Theoretical Frameworkmentioning
confidence: 99%
“…Remote teaching has been used across all subject areas of education, particularly during the global pandemic. Institutions have created infrastructures for online education, and several educational institutions have completed entire academic calendars using remote teaching (Özdemir, Yıldız & Şahan, 2021). Internet technologies may have a positive impact on students by providing them with timely access to information and updated resources in their areas.…”
Section: Discussionmentioning
confidence: 99%
“…The findings of a recent study that was conducted during the COVID-19 pandemic showed that smartphones are used frequently for e-learning, but at the same time, being connected to technological tools increases the risk of engaging in activities that are not related to the course content, which might lead to cyberloafing behaviours (Ozdemir et al, 2021). During students' educational activities, the efficiency and productivity in learning are affected by cyberloafing activities due to the use of smartphones during classes (Saritepeci, 2020).…”
Section: Introductionmentioning
confidence: 99%